2011
DOI: 10.1002/term.461
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-conditioned medium facilitates angiogenesis and fracture healing in diabetic rats

Abstract: The most critical factor for fracture union is the blood supply to the fracture site, which is usually impaired in patients with diabetes. Recently, mesenchymal stem cells-derived conditioned medium (MSC-CM) has shown significantly higher levels of angiogenic factors, such as VEGF and IL-6. We demonstrate in this report that MSC-CM delivered in gelatin sponges stimulates angiogenesis and promotes fracture healing in a diabetic rat model. Subcutaneous implantation of gelatin sponges soaked in MSC-CM demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 31 publications
5
65
0
1
Order By: Relevance
“…Furthermore, we found that MSC exosomes were uptaken by HUVECs and enhanced endothelial angiogenesis in vitro. This latter finding is in line with several reports demonstrating the angiogenic potential of MSC-conditioned medium [61][62][63], and a recent report by Bian et al that examined the angiogenic effects of MSC exosomes [64].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we found that MSC exosomes were uptaken by HUVECs and enhanced endothelial angiogenesis in vitro. This latter finding is in line with several reports demonstrating the angiogenic potential of MSC-conditioned medium [61][62][63], and a recent report by Bian et al that examined the angiogenic effects of MSC exosomes [64].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, Osugi et al reported a higher evaluation of new bone regeneration in the MSC-CM group compared with the control and the MSC transplanted groups after 4, and 8 weeks (24). In another study, Wang et al demonstrated that MSC-CM delivered in gelatin sponge increased angiogenesis and bone regeneration in a diabetic rat model (49). We applied a different approach for quantitative comparison between studied groups using three dimensional stereological analysis to determine more reliable results.…”
Section: Discussionsupporting
confidence: 92%
“…Angiogenesis also plays an important role in fracture healing [46]. CM contains high levels of angiogenic factors such as VEGF and IL-6 and enhances bone ingrowth and fracture healing by stimulating endothelial cells [47]. However, as we previously reported, although VEGF and IL-6 levels in MSC exosomes are low compared with CM and CM-Exo, MSC exosomes induce angiogenesis to a greater extent [36].…”
Section: /2mentioning
confidence: 77%